Crime Prevention Strategies of Bangladesh: An Analysis - Akter, Mahmuda (American Journal of Trade and Policy, 2018)
The need to address crime is as old as civilization itself, and while we have always struggled with whether to punish or rehabilitate criminal activity, there has never been any question that the best alternative to ‘crime’ is prevention. The main objective of this study was to identify an alternative analysis of possible effective crime prevention strategies suitable for the socio-economic premises of Bangladesh. Moreover, the study also tried to find out the necessary action for implementation of crime prevention strategies. The comprehensive discussion based on secondary sources as well as documents like journal articles, authentic books. This study finds out the fields of crime prevention include a range of responses developed over many years, includes developmental, environmental, situational, social and community-based crime prevention, and interventions. Although theoretically there are very few crime prevention strategies in Bangladesh in practice, there are various strategies for crime prevention used here institutionally or un-institutionally which includes community-oriented policing and various security measures. Investing in crime prevention could reduce the drawbacks of the conventional criminal justice system. If the crime prevention strategies could ensure properly, crime and criminal victimization could prevent which will reduce the need for formal criminal justice system in Bangladesh.